2005
DOI: 10.1074/jbc.m506575200
|View full text |Cite
|
Sign up to set email alerts
|

Acute Glutathione Depletion Restricts Mitochondrial ATP Export in Cerebellar Granule Neurons

Abstract: Decreases in GSH pools detected during ischemia sensitize neurons to excitotoxic damage. Thermodynamic analysis predicts that partial GSH depletion will cause an oxidative shift in the thiol redox potential. To investigate the acute bioenergetic consequences, neurons were exposed to monochlorobimane (mBCl), which depletes GSH by forming a fluorescent conjugate. Neurons transfected with redox-sensitive green fluorescent protein showed a positive shift in thiol redox potential synchronous with the formation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 57 publications
5
83
0
Order By: Relevance
“…In contrast, higher concentrations of GSSG (100 M) inhibit ADP/ATP translocation by ANT (Fig. 7A), which is in agreement with the findings of Vesce et al (40), who have shown that acute GSH depletion decreases ATP transport through the inner membrane.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, higher concentrations of GSSG (100 M) inhibit ADP/ATP translocation by ANT (Fig. 7A), which is in agreement with the findings of Vesce et al (40), who have shown that acute GSH depletion decreases ATP transport through the inner membrane.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, studies with CGNs have shown that the bioenergetic failure associated with DCD causes a dramatic increase in O 2 ⅐Ϫ levels in the deregulated cells (Vesce et al, 2004). Additionally, oxidative stress induced by acute glutathione depletion restricts CGN ATP generation by inhibiting mitochondrial ATP export to the cytoplasm (Vesce et al, 2005). As confirmed in Figure 1, oxidative stress, or at least an increase in matrix O 2 ⅐Ϫ levels, occurs in the presence of even low nanomolar concentrations of rotenone.…”
Section: Discussionmentioning
confidence: 54%
“…It is established that energetic insufficiency can exacerbate excitotoxicity , and, in this study, the ability to monitor the respiration of coverslip-attached neurons has allowed us to test the contribution of oxidative stress and respiratory insufficiency to the rotenone-enhanced cell death associated with chronic NMDA receptor activation in primary cultures of rat cerebellar granule neurons (CGNs). It must be emphasized that the conclusions apply specifically in the context of glutamate excitotoxicity and that because oxidative stress can damage ATP generating capacity (Vesce et al, 2005), it should not be assumed that these are mutually opposing concepts.…”
Section: Introductionmentioning
confidence: 99%
“…GSH is the major regulator of cellular redox status due to its high concentration, reductive potential, and involvement in quenching oxidative stress (50). Covalent modification of proteins with GSH is also emerging as a key post-translational modification required for protein regulation in response to changes in redox environment.…”
Section: Discussionmentioning
confidence: 99%